2020
DOI: 10.7860/jcdr/2020/45329.13945
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Preventive Oral Health Measures among Special Care School Children (boys) in Al-Kharj, Saudi Arabia

Abstract: Introduction: Special needs children experience poorer oral health when compared to their compatriots. Moreover, Special Care School Children (SCSC) experience significant barriers to access proper oral health care. It has been found that they have high unmet oral health needs. Aim: The aim of this study was to assess the effectiveness of preventive oral health measures in a group of SCSC; boys, in Al-Kharj Governorate of Saudi Arabia. Materials and Methods: A longitudinal study was designed among SCSC in Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Thirty-five studies were cross-sectional [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 50 , 51 ], one was a longitudinal study [ 45 ], and two were retrospective studies [ 28 , 49 ]. Twenty-two studies were conducted in or near Riyadh [ 10 , 11 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 38 ...…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations